2017
DOI: 10.1007/s10291-016-0598-x
|View full text |Cite
|
Sign up to set email alerts
|

Observations of quiet-time moderate midlatitude L-band scintillation in association with plasma bubbles

Abstract: Observations of moderate night time amplitude scintillation on the GPS L1C/A signal were recorded at the midlatitude station of Nicosia, corresponding geographic latitude and longitude of 35.18°N and 33.38°E respectively, on a geomagnetically quiet day. The variations of slant total electron content (STEC) and amplitude scintillation index (S4) on the night of June 12, 2014, indicate the presence of electron density depletions accompanying scintillation occurrence. The estimated apparent horizontal drift veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The signal intensity attenuation led by ionospheric anomaly can be observed with the SNR measurements (Bong et al, 2015; He et al, 2016; Vadakke Veettil et al, 2017). Even more, the attenuation will affect the accuracy of pseudorange to some degree.…”
Section: Positioning Performance With Multi‐gnssmentioning
confidence: 95%
“…The signal intensity attenuation led by ionospheric anomaly can be observed with the SNR measurements (Bong et al, 2015; He et al, 2016; Vadakke Veettil et al, 2017). Even more, the attenuation will affect the accuracy of pseudorange to some degree.…”
Section: Positioning Performance With Multi‐gnssmentioning
confidence: 95%
“…On the model development at these latitudes, the statistical test described in Section 2 indicated that none of the estimated coefficients were statistically significant, leading to conclude that any attempt using our approach to develop a model specific for the mid-latitudes would be meaningless. Nevertheless, during weak scintillation periods at the mid-latitude station of CYP, the variations in S4 are more pronounced than the variations in r u (Vadakke Veettil et al, 2017) Therefore, the models developed for the low latitudes were tested at this station. Concurrently, at the European mid-latitude station NOT, during weak scintillation periods the variations in r u are more pronounced than the variations in S4 (Aquino et al, 2005).…”
Section: Mid-latitude Modelmentioning
confidence: 99%
“…Compared to its equatorial and polar counterparts, the midlatitude ionosphere is less affected by ionospheric irregularities [10]. Scintillation patches (S 4 ) noted in GNSS trans-ionospheric links, as a consequence of ionospheric irregularities, over the nighttime midlatitude ionosphere, are not as frequent [11] except during disturbed geomagnetic conditions. The midlatitude nighttime F region is characterised by multiple diffused patterns of plasma structure irregularities, which may last from a few minutes to several hours, referred to as midlatitude spread F [12][13][14][15].…”
Section: Introductionmentioning
confidence: 97%